Digitalizing Multiple Intelligence Assessment in Early Childhood: A Needs Analysis from Teachers' Perspectives - Dita Masdalena; Tri Milda Alfudjar; Lina Amelia; Aina Nabila Nabila (Journal of Early Childhood Education Research, 2025)
Purpose: The digitalization of assessment instruments has become critical in early childhood education, yet implementation gaps persist. Multiple intelligence assessment continues to rely on manual methods that are time-consuming and prone to errors. This study analyzes the needs for digitalizing multiple intelligence assessment from teachers' perspectives, examining current practices, technological readiness, perceived benefits and barriers, and requirements for user-friendly digital systems. Methodology: A qualitative exploratory case study was conducted at Khalifah 3 Islamic Kindergarten, Indonesia, during 2024/2025. Data were collected through semi-structured interviews with early childhood teachers as primary assessment implementers. Interviews explored current assessment practices, perceptions of digital technology, digital literacy levels, and digitalization needs. Data were analyzed thematically using Technology Acceptance Model (TAM) and Diffusion of Innovations theory as analytical frameworks. Results: Findings reveal that the kindergarten has not implemented multiple intelligence assessment, with evaluation focused on standard Child Development Achievement Standards (STPPA). Teachers demonstrated positive perceptions toward digital tools with high perceived usefulness regarding time efficiency, documentation ease, improved accuracy, and collaborative capabilities. However, implementation faces constraints including limited digital literacy in advanced spreadsheet functions, inadequate technological infrastructure with insufficient devices and unstable connectivity, and absence of technical support, indicating low perceived ease of use. Conclusions: Based on TAM and Diffusion of Innovations frameworks, the kindergarten is in early technology adoption stages (knowledge and persuasion phases). The contrast between high perceived usefulness and low perceived ease of use indicates recognition of digital benefits but lack of implementation capabilities. Successful digitalization requires comprehensive institutional support including intensive digital literacy training, enhanced technological infrastructure, ongoing technical assistance, and user-friendly assessment templates. Digital transformation must follow a gradual approach encompassing digitalization roadmaps, continuous professional development, and sustained mentoring systems. These findings illuminate the gap between digital assessment potential and implementation reality, offering evidence-based recommendations for supporting teachers' transition to technology-enhanced assessment in resource-constrained contexts.